1989
DOI: 10.1039/p29890001167
|View full text |Cite
|
Sign up to set email alerts
|

Selective extraction and transport of UO2 2+ with calixarene-based uranophiles

Abstract: Hexacarboxylate derivatives of p-t-butylcalix [6]arene (2b) and p-hexylcalix[6]arene (3b) extract uranyl ion (UO;+) efficiently and selectively from water into organic media. This high selectivity can be attributed to the nature of calix [6]arene; this is suitably structured for the binding of U02'+, which requires a pseudoplanar h exacoord i nation . When t r i octy I met h y I a m mo n i u m cation (T M A + ) is added to the organic phase, the stoicheiometry of the extraction species [U02'+/(2b)] changes fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
73
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 3 publications
(8 reference statements)
1
73
0
Order By: Relevance
“…2,13 In particular, efforts have been directed toward selective molecular recognition of uranyl ion with macrocyclic host molecules including crown ethers and calixarenes. [2][3][4]7,[13][14][15][16] In a previous study, 17 we found that 2,2Ј-dihydroxyazobenzene (DHAB) (1) forms a 1 : 1-type complex with uranyl ion. The pH dependence of log K f for the uranyl complex (2) of a DHAB derivative revealed that ionization of the phenol groups and the uranium-bound water molecule facilitate uranyl binding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,13 In particular, efforts have been directed toward selective molecular recognition of uranyl ion with macrocyclic host molecules including crown ethers and calixarenes. [2][3][4]7,[13][14][15][16] In a previous study, 17 we found that 2,2Ј-dihydroxyazobenzene (DHAB) (1) forms a 1 : 1-type complex with uranyl ion. The pH dependence of log K f for the uranyl complex (2) of a DHAB derivative revealed that ionization of the phenol groups and the uranium-bound water molecule facilitate uranyl binding.…”
Section: Introductionmentioning
confidence: 99%
“…The design of effective host molecules for uranyl ion is connected with the economic importance of selective extraction [1][2][3][4] of uranium from seawater as well as the development of therapeutic agents 5 for removal of uranyl ion from human bodies. Uranium exists mainly as the tricarbonate complex of uranyl ion [UO 2 (CO 3 ) 3 4Ϫ ] in seawater.…”
Section: Introductionmentioning
confidence: 99%
“…Izatt et al 4 first reported on the extraction of alkaline metal ions with a calixarene; then, novel calixarene ligands have been synthesized for the extraction of several metal ions. [5][6][7][8][9] In a previous paper we reported on the extraction behavior of rare-earth metals with a calixarene derivative functionalized by carboxyl groups. 10 In the present study, we investigated the extraction behavior of twelve kinds of metal ions, such as alkaline (Li, Na, K, Cs), alkaline-earth (Mg, Ca, Sr, Ba) and transition-metal ions (Cu, Zn, Co, Ni) with two cyclic compound calixarenes (o-carboxylate derivatives of p-toctylcalix[n]arene (n=4,6)) along with the monomer analog (n=1).…”
mentioning
confidence: 99%
“…1 Shinkai et al have shown that carboxyl and hydroxamate derivatives of 16 could extract UO2 2+ with higher extractability and selectivity than those of 14 derivatives. [2][3][4][5][6] On the other hand, they first synthesized water-soluble calix[n]arenes, 2n, in 1987, and reported that 26 is a metal ligand that has a high affinity to UO2 2+ in stability and selectivity, and named it "superuranophile". 7 We studied their reaction with various metal ions, including proton in aqueous solution.…”
mentioning
confidence: 99%